2022
DOI: 10.53730/ijhs.v6ns6.10529
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous changes during pregnancy

Abstract: Objectives: This present study was to evaluate the various dermatological manifestation during pregnancy. Methods: A detailed history including chief complaints related to skin, onset in relation to duration of pregnancy, complete general physical & systemic examinations, associated skin / medical disorders were performed to all patients. Investigations-CBC, OGTT, TSH, VDRL, HIV, HBsAg, Anti-HCV, Urine routine examination, LFT, S. Bile Acids, KOH mount, Skin biopsy and DIF were done wherever required. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…4 Ali et al also showed a similar incidence of (1.5%) of patients having acrochordon. 24 This is more common in third trimester which is concordant with our study. Non-specific disorders were common in multigravida during third trimester which were concordant with Latha and Haritha study.…”
Section: Pathological Non-specific Dermatosessupporting
confidence: 93%
“…4 Ali et al also showed a similar incidence of (1.5%) of patients having acrochordon. 24 This is more common in third trimester which is concordant with our study. Non-specific disorders were common in multigravida during third trimester which were concordant with Latha and Haritha study.…”
Section: Pathological Non-specific Dermatosessupporting
confidence: 93%